An analysis of whether the Two‐Pillar Solution is an equitable solution for developing countries in addressing tax challenges of a digital economy - Van Dyk, Tertia (University of the Witwatersrand, Johannesburg, 2022)
The purpose of this research report is to determine whether key elements of the Organisation for Economic Co‐operation and Development (OECD) Two‐Pillar Solution are equitable to developing countries. The key principles contained in the Two‐Pillar Solution will be critically discussed to determine whether these rules are designed in a manner that: I. Allows for appropriate and acceptable tax competition for developing countries to fairly compete with larger economies; and II. Ensures that multinational enterprises pay adequate tax in the developing countries where they operate, extract value and generate profits. The report seeks to understand who the key role players are, what base erosion and profit shifting (BEPS) challenges have arisen caused by the digitalisation of the global economy, and how the OECD Two‐Pillar Solution seeks to address these challenges. This analysis is conducted through the lens of developing countries, which are vulnerable to inequitable allocation of taxing rights. The report seeks to assess whether the key elements of the Two‐Pillar Solution are consistent with existing international tax rules that govern the allocation of taxing rights and, in some instances, challenges whether the existing rules on international tax are equitable to developing countries in the first place. The role of tax policy and tax competition from the perspective of developing countries will be discussed. Finally, the effectiveness of alternative mechanisms to address tax abuse will be assessed, including digital services tax and controlled foreign company rules, will be examined. Key Words: Multinational enterprises, base erosion and profit shifting, BEPS, inclusive framework, Global Anti‐Base Erosion Model, developing countries, tax incentives, controlled foreign company rules, effective tax rate, low‐taxed income, G20, digital services tax, Organisation for Economic Co‐Operation and Development
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfillment of the requirements for the degree of Master of Commerce in the field of Taxation, University of the Witwatersrand, Johannesburg, 2022
Keywords: UCTD; Multinational enterprises; Base erosion and profit shifting; BEPS; Inclusive framework; Global Anti‐Base Erosion Model; Developing countries; Controlled foreign company rules; Low‐taxed income; Digital services tax; Organisation for Economic Co‐Operation and Development; SDG-8: Decent work and economic growth